2018
DOI: 10.1182/blood-2018-99-117098
|View full text |Cite
|
Sign up to set email alerts
|

P38α/JNK Signaling Restrains Erythropoiesis By Suppressing Ezh2-Mediated Epigenetic Silencing of Bim

Abstract: A remarkable feature of erythropoiesis is the coordination of proliferation, differentiation and apoptosis of erythroid cells to precisely achieve erythropoietic homeostasis to avoid anemia and polycythemia. Anemia is a common disease arising from various causes, including Myelodysplastic syndromes, thalassemia, cancer chemotherapy, chronic kidney disease and hemorrhage. The pro-erythropoietic factor erythropoietin (EPO) is often employed for anemia therapy. However, questions have been raised about the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Gerwins et al showed that MAP3K4 knockdown activated JNKs selectively without any effect on p38 or ERK in human embryonic kidney cells, 57 while others found that MAP3K4 deficiency specifically reduced p38 phosphorylation without any effect on JNK or ERK in CD4 T cells and male gonad samples 23,58 . Meanwhile, Hu et al discovered that MAP3K4 knockdown ablated p38α deficiency‐induced activation of JNK phosphorylation in erythroblasts of p38α knockout mice 96 . Hence, MAP3K4 exhibits diverse cellular functions in different cell types, dependent on the different substrates of MAP3K4 and interconnection of MAPK regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Gerwins et al showed that MAP3K4 knockdown activated JNKs selectively without any effect on p38 or ERK in human embryonic kidney cells, 57 while others found that MAP3K4 deficiency specifically reduced p38 phosphorylation without any effect on JNK or ERK in CD4 T cells and male gonad samples 23,58 . Meanwhile, Hu et al discovered that MAP3K4 knockdown ablated p38α deficiency‐induced activation of JNK phosphorylation in erythroblasts of p38α knockout mice 96 . Hence, MAP3K4 exhibits diverse cellular functions in different cell types, dependent on the different substrates of MAP3K4 and interconnection of MAPK regulatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, its role in adipogenesis seems to depend on the cellular system analysed, with reports of both stimulating and inhibitory effects 27,138,139 . p38α also restrains erythropoiesis through the repression of MEKK4 to keep JNK activity low, resulting in erythroblast apoptosis 145 . Likewise, the TGFβ-induced differentiation of mesenchymal stem cells into endothelial-like cells is negatively regulated by p38α via TAK1 and JNK inhibition 146 .…”
Section: Bcl-2 Family Proteinsmentioning
confidence: 99%
“…another major stress-responsive mitogen-activated protein kinase (MaPK) pathway, the JNK1/2 pathway, has been consistently found to be negatively regulated by p38α in different contexts 2 . importantly, the enhanced JNK activity observed in several cell types upon p38α inhibition or downregulation is likely to be relevant in vivo, as the phenotypes observed upon p38α downregulation sometimes can be ascribed to the concomitant JNK upregulation 145,146 , and differences in JNK activity levels may provide a source of cell-to-cell heterogeneity when targeting p38α 42 . Paradoxically, the p38α and JNK pathways are often simultaneously activated in response to stress 5 , as they share numerous upstream MaP3K activators, such as taK1, MLK3 or asK1, but can potentially display opposing functions, suggesting that the dynamic balance between p38α and JNK signalling is essential for cell homeostasis.…”
Section: Box 2 | Interplay Between P38 Kinases and Other Signalling Rmentioning
confidence: 99%